2004
DOI: 10.1002/art.20584
|View full text |Cite
|
Sign up to set email alerts
|

The presence of citrullinated proteins is not specific for rheumatoid synovial tissue

Abstract: Objective. Antibodies directed toward citrullinated proteins (e.g., anti-cyclic citrullinated peptide antibodies) are highly specific for rheumatoid arthritis (RA) and are produced locally at the site of inflammation. Although the presence of citrullinated proteins in rheumatoid synovium has been described in the literature, it is uncertain whether their presence is specific for RA. The present study was undertaken to investigate this.Methods. The local production of the anticitrullinated protein antibodies wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
145
1
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(163 citation statements)
references
References 31 publications
8
145
1
9
Order By: Relevance
“…Finally, the relationship between intracellular citrullinated proteins and ACPAs was stronger locally in SF than systemically in serum, with higher SF than serum ACPA levels in intracellular citrullinated protein-positive but not intracellular citrullinated protein-negative joints. Since this cannot be fully explained by immobilization of ACPAs by complex formation with citrullinated targets in the joints, these data are consistent with the previous demonstration of local ACPA production (14,49) and also suggest that this could be driven by specific synovial deiminated proteins.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, the relationship between intracellular citrullinated proteins and ACPAs was stronger locally in SF than systemically in serum, with higher SF than serum ACPA levels in intracellular citrullinated protein-positive but not intracellular citrullinated protein-negative joints. Since this cannot be fully explained by immobilization of ACPAs by complex formation with citrullinated targets in the joints, these data are consistent with the previous demonstration of local ACPA production (14,49) and also suggest that this could be driven by specific synovial deiminated proteins.…”
Section: Discussionsupporting
confidence: 89%
“…The relevance of this finding is emphasized by several facts. First, previous studies failed to demonstrate a link between ACPAs and non-RA-specific citrullinated proteins, including fibrin (20,49). Second, our findings indicated that the presence of intracellular citrullinated proteins is independent of the degree of synovial inflammation and that the demonstrated link with ACPAs is thus not merely a secondary phenomenon due to higher ACPA levels leading to enhanced inflammation.…”
Section: Discussionmentioning
confidence: 44%
“…It appears that the presence of citrullinated proteins in inflamed synovium is not specific for RA, but rather may be an inflammation-associated phenomenon (40). Independent of disease duration, synovitis in patients with anti-CCP-positive RA differs from that in patients with anti-CCP-negative RA, notably with respect to increased infiltrating lymphocytes and higher rate of local joint destruction (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the accumulation of citrullinated proteins has been described at sites of inflammation, including the joints of patients with all forms of arthritis (17), the brains of patients with multiple sclerosis (18) or Alzheimer's disease (19), and in the muscle fibers of patients with myositis (20). Hence, citrullinated proteins are present in the setting of both health and disease, while tolerance to citrullinated proteins appears to be selectively lost in patients with RA.…”
mentioning
confidence: 99%